The effect of self-efficacy and self-set grade goals on academic outcomes - Saks, Katrin (Frontiers in Psychology, 2024)
Numerous motivational research have clearly demonstrated the critical role of self-processes in goal setting, self-regulated learning, and learning outcomes. However, studies have emerged that present conflicting findings regarding the relationship between goal setting and self-efficacy and how it affects academic performance. Based on the theories of goal setting and self-efficacy, the purpose of this paper is to assess the predictive power of self-efficacy and the mediating effect of self-set grade goals on learning outcomes. As part of the online course, an exploratory study was conducted with a sample of 160 university teacher training students. Data on self-efficacy were collected with the MSLQ and analyzed with confirmatory factor analysis. Correlation analysis explored the relationships between motivational factors, grade goals, and learning outcomes. To test the models, structural equation analysis was conducted to predict the effect of self-efficacy on self-set grade goals and learning outcomes. The results showed the predictive effect of self-efficacy on expected and minimum grade goals and the mediating effect of expected grade goal on learning outcomes. The study highlights the influence of motivational factors on goal setting in the context of online learning and provides insight into the predictive effect of self-efficacy on learning outcomes.